Penerapan Pewarnaan Graf Pada Penjadwalan Mata Kuliah Program Studi Matematika UIN Imam Bonjol Padang - Novita Hasanah; Raudhatul Jannah; Mohamad Syafii; Lilis Harianti Hasibuan (UIN Imam Bonjol Padang, 2022)
A graph is a discrete structure consisting of vertices and edges connecting these vertices. One of the discussions in graph theory is graph coloring. In this research, graph coloring will be applied in making the schedule for the Mathematics study program at UIN Imam Bonjol Padang by assuming the subject as a vertice and the lecturer as an edge. One of the benefits of applying graph coloring in scheduling makes scheduling arrangements easier. The graph coloring algorithm use the Welsh Powell Algorithm. Based on the application of graph coloring with the Welsh Powell Algorithm obtained the lecturer's teaching schedule according to the SKS, time and classroom given.